2018
DOI: 10.18203/2319-2003.ijbcp20181186
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of adverse drug reactions in medicine, paediatric and surgical departments of a tertiary care hospital: a prospective observational study

Abstract: Background: the aim of the study was to monitor all adverse drug reactions in the departments of Medicine, Paediatrics and Surgery in a Tertiary Care Hospital.Methods: It was a prospective study undertaken in a 300 bedded tertiary care hospital. Patients presenting with adverse drug reactions in Medicine, Paediatrics and Surgery Departments were studied. Causality and severity of the adverse drug reactions were analysed Other parameters such as age wise and gender wise distribution of the ADRs, types of ADRs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This result was in concordance with the results of several previous studies, while few studies also showed male preponderance. [6][7][8][9][10][11] Women experience adverse reactions more frequently than men do. This finding may be because women and men show different pharmacokinetic and pharmacodynamic responses to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in concordance with the results of several previous studies, while few studies also showed male preponderance. [6][7][8][9][10][11] Women experience adverse reactions more frequently than men do. This finding may be because women and men show different pharmacokinetic and pharmacodynamic responses to drugs.…”
Section: Discussionmentioning
confidence: 99%